Perkawinan Paksa antara Korban dan Pelaku Pemerkosaan dalam Perspektif Hak Asasi Manusia Berperspektif Gender dan Restorative Justice - Trianti Rizka Kusumawardhini (CV Rewang Rencang, 2025)
Sexual violence against women is one of the issues that should be a concern in Indonesia. It is characterized by a high number of cases of sexual violence against women. One form of injustice that often occurs is the practice of forced marriage between rape victims and perpetrators who are often justified in the name of “restorative justice”. In fact, this practice is contrary to the principles of human rights (HR), positive law, as well as the basic values of restorative justice itself. This study uses normative juridical methods to examine the practice of forced marriage between perpetrators and victims of sexual violence cases based on the perspective of human rights and gender as well as the principles of restorative justice. The results showed that the forced marriage of victims with perpetrators is an advanced form of gender-based violence that injures women's rights and reduces the meaning of Justice. The state needs to ensure that the application of restorative justice is not mistaken for the legitimacy of a “peaceful” settlement that actually harms victims. Therefore, strengthening the understanding of law enforcement officers, strict supervision, as well as legal protection in favor of the victim is an urgency that cannot be ignored.